"Interlocking" Clipping of an Irregular Middle Cerebral Artery Bifurcation Aneurysm: 2-Dimensional Operative Video. Issue 2 (30th May 2018) - Sorenson, Thomas J; Marcellino, Chris; Acciarri, Nicola; Rangel Castilla, Leonardo; Lanzino, Giuseppe
Abstract: Middle cerebral artery (MCA) aneurysms often have an irregular morphology that might require creative clipping techniques even in the case of small aneurysms. In this video, we illustrate the case of a patient with an incidental but very irregular MCA aneurysm. The presence of 2 separate, asymmetric lobes was dealt with by utilizing the "interlocking" clip technique in which a regular clip is used to obliterate 1 portion of the aneurysm and a fenestrated clip, with the ring of the fenestration circling the body of the first clip, is used to obtain obliteration of the other lobe. This patient also had a contralateral internal carotid artery occlusion, and we discuss the pitfalls of temporary clipping in such a situation.